Jabal al-ʿAluya: an inland Neolithic settlement of the late fifth millennium BC in the Ādam area, Sultanate of Oman - Lemée, Marion; Gernez, Guillaume; Giraud, Jessica; Beuzen-Waller, Tara; Fouache, Éric (Proceedings of the Seminar for Arabian Studies, 2013)
Jabal al-ʿAluya is a Neolithic site located at the foot of Jabal Salekh near Ādam, Sultanate of Oman. The evidence of dispersed occupation across the 65 ha of the site comprises 139 structures and lithic concentrations, including numerous Neolithic bifacial chert tools. Excavation of a U-shaped stone-hut dwelling in one of the three main zones of occupation at the site recorded post holes, a fireplace, and a pit with what is believed to be a grinding tool. The site is close to water and raw material sources, and geomorphological studies show that it is well preserved despite deflation. The location of the settlement in the inland region of Oman makes it all the more interesting and significant for our understanding of the Neolithic period in south-eastern Arabia, as almost all Neolithic sites excavated to date are located near the coastline.